Efeito probiótico da bactéria Escherichia coli linhagem nissle 1917 em modelo murino de colite ulcerativa induzida por sulfato de sódio dextrano (DSS) - Éricka Lorenna de Sales e Souza (2013)
The inflammatory bowel diseases (IBD) are chronic inflammatory processes that affect the gut of susceptible individuals. One of its main forms, ulcerative colitis (UC), is restricted to the colonic mucosa and is characterized clinically by weight loss, rectal bleeding and diarrhea. Such manifestations present periods of remissions and relapses, and there is no cure. The attention now to the treatment of UC is facing probiotics, among which Escherichia coli Nissle 1917 (EcN) deserves great prominence by presenting comparable effects to the drug of choice in the treatment of mild to moderate UC, mesalazine. The aim of this study was to evaluate the effect of the EcN probiotic in a murine model of UC induced by Dextran Sulfate Sodium (DSS). For this, we used female BALB/c mice with induced colitis (3.5% DSS solution) for 7 days. There was a significant improvement between the groups treated and not treated with the probiotic in clinical signs of disease. The inflammatory state generated was significantly reduced, with a decrease in the recruitment of neutrophils and eosinophils to the focus of inflammation, without, however, observed changes in the levels of macrophages. The intestinal permeability, which is typically increased during the onset of IBD, tended to a reduction after treatment with EcN. Histological analysis regarding the preservation of the intestinal epithelium, the beneficial effect of the probiotic can be observed in 67% of the samples (n 2 in 3).No difference was observed in the rates of reactive oxygen species produced in DSS model after the treatment with the probiotic. The analyzis showed that the probiotic EcN model has beneficial effect in acute UC, however further analysis are necessary in order to investigate the mechanisms by which this effect is realized.